Macromol. Rapid Commun. 18/2010 - Schumers, Jean-Marc; Fustin, Charles-André; Gohy, Jean-François (Macromolecular rapid communications., 2010)
Back Cover: The picture presents stimuli‐responsive polymers, which are able to show responses to various environmental changes. Among those stimuli, light has attracted much attention since it can be localized in time and space, and it can also be triggered from outside the system. In the related feature article, light‐responsive block copolymers are reviewed. Further details can be found in the article by J.‐M. Schumers, C.‐A. Fustin,* and J.‐F. Gohy* on page 1588.